2012
DOI: 10.1071/cp11279
|View full text |Cite
|
Sign up to set email alerts
|

Drought-tolerance indices in a tall fescue population and its polycross progenies

Abstract: Development of drought-tolerant cultivars is hampered by a lack of effective selection criteria. In this research, drought tolerance of 75 genotypes of tall fescue in three sets (25 parental, 25 early, 25 late-flowering progenies) was evaluated under no soil moisture stress and soil moisture stress in the field during 2009 and 2010. Five drought-tolerance indices were calculated: stress tolerance (TOL), mean productivity (MP), geometric mean productivity (GMP), stress susceptibility index (SSI), and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…In the experiments carried out by Ebrahimiyan et al. (), STI values ranged from nearly 0 to about 4. In our set of Lp populations , the highest recorded STI value was about 3 (involving root DM), a value which should be a sufficient basis for effective selection of drought tolerant genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…In the experiments carried out by Ebrahimiyan et al. (), STI values ranged from nearly 0 to about 4. In our set of Lp populations , the highest recorded STI value was about 3 (involving root DM), a value which should be a sufficient basis for effective selection of drought tolerant genotypes.…”
Section: Discussionmentioning
confidence: 94%
“…After developing a broad-based population from polycross of a set of 25 parental tall fescue genotypes (Majidi et al 2009), 24 (eight early-, eight mid-, and eight late-season flowering) genotypes were selected within the progenies based on drought tolerance and susceptibility indices (Ebrahimiyan et al 2012). The genotypes were clonally propagated in a greenhouse and then transferred to the field in March 2011.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Instances are stress tolerance index (STI) introduced by Fernandez (1992), which can be used to identify genotypes that produce high yields under both stress and non-stress conditions, and tolerance index (TOL) introduced by Rosielle and Hamblin (1981) based on differences in yields measured under nonstress and stress conditions. Using drought tolerance and susceptibility indices, Ebrahimiyan et al (2012) assessed drought tolerance of 75 tall fescue genotypes in three different flowering sets. Nevertheless, little information is still available about the relationship between these indices and root and physiological traits.…”
Section: Introductionmentioning
confidence: 99%
“…Ebrahimiyan et al . (,b) suggested that indirect selection for developing high‐yielding, drought‐tolerant varieties should be conducted under drought stress conditions. Previous studies reported that plants such as tall fescue respond and adapt to drought stress using a variety of mechanisms including escape, avoidance and tolerance, all of which serve to improve the efficiency of water uptake and minimize water loss (Wang and Huang, ; Pirnajmedin et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Ebrahimiyan et al . (,b) reported that selection based on indices such as STI is a suitable approach for screening drought tolerance and sustainable tall fescue genotypes with a high positive correlation between STI index and drought tolerance (Talebi et al ., ; Ebrahimiyan et al ., ).…”
Section: Introductionmentioning
confidence: 99%